2010
DOI: 10.1161/strokeaha.110.586289
|View full text |Cite
|
Sign up to set email alerts
|

High von Willebrand Factor Levels Increase the Risk of Stroke

Abstract: Background and Purpose-Many studies have investigated the role of plasma von Willebrand factor level in coronary heart disease, but few have investigated its role in stroke. The aim of this study was to determine if von Willebrand factor levels are associated with the risk of stroke. Methods-The study was part of the Rotterdam Study, a large population-based cohort study among subjects aged Ն55 years. We included 6 250 participants who were free from stroke at baseline (1997 to 2001) and for whom blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
93
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(110 citation statements)
references
References 35 publications
8
93
0
6
Order By: Relevance
“…In this large population study of British men aged 60 to 79 years, we have confirmed the findings of some previous prospective studies 9,10,13,14 that circulating levels of hemostatic markers are associated with incident stroke. We have shown that fibrin D-dimer and vWF, but not tPA antigen, are independently associated with incident stroke in older men and their measurements modestly improved prediction of stroke as assessed by improvement in the C statistics.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this large population study of British men aged 60 to 79 years, we have confirmed the findings of some previous prospective studies 9,10,13,14 that circulating levels of hemostatic markers are associated with incident stroke. We have shown that fibrin D-dimer and vWF, but not tPA antigen, are independently associated with incident stroke in older men and their measurements modestly improved prediction of stroke as assessed by improvement in the C statistics.…”
Section: Discussionsupporting
confidence: 89%
“…4 The von Willebrand factor (vWF) is synthesized primarily by vascular endothelial cells and promotes platelet adhesion and aggregation, leading to thrombus formation. 1 Increased levels of vWF in stroke patients have been reported in several case-control studies, [5][6][7][8] but prospective studies have been inconsistent, with some showing a positive relationship 9,10 and others showing no relationship [11][12][13][14] between vWF and stroke risk. Fibrin D-dimer is the primary degradation product of cross-linked fibrin and is a marker of activated coagulation and fibrinolysis.…”
mentioning
confidence: 99%
“…10,25 Several studies have reported an association between high vWF levels and the risk of ischemic stroke. 11,43,44 We found increased vWF levels, vWF activity, and vWF HMWMs in patients with acute stroke . High plasma levels of vWF are regarded as a biomarker of endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 66%
“…7,8 Elevated vWF concentrations are associated with cardiovascular disease, 9 increased risk of ischemic heart disease, and the occurrence of acute ischemic stroke 10 ; these high levels of vWF are associated with the risk of stroke, even in the general population. 11 The biological function of vWF depends largely on the size of its multimers. 12 High-molecular-weight multimers (HMWMs) are the most efficient in hemostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the level of vWF in plasma is considered to be a signalling factor of endothelial dysfunction, a condition that predisposes to atherosclerosis and thrombosis. Because of its direct role in hemostasis, and its indirect role as a signalling factor of endothelial dysfunction, vWF is a potential risk indicator for cerebrovascular disease (Wieberdink et al, 2010).…”
mentioning
confidence: 99%